Project 2 : There- Sites of Korean Diaspora - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2002)
29 Mar- 29 Jun 2002. Project 2: 'There: Sites of Korean Diaspora' offers insights into the unique qualities of the broader global history and dynamics of the Korean diaspora while at the same time focusing on five key cities of significant Korean diasporic population that are also diverse hsitorically and geographically: Los angeles, Sao Paulo, Almaty, Yanji, Osaka. Critical reflections on the current global situation of contemporary art. An event city created through close, interactive collaborations and diverse interventions among the artist, architect and curators.
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions